Influence Of Azolla Composition (Azolla, Sp) On The Growth Of Oil Family Bitches (Elaeis Quenensis Jacq) In Pre Nursery - Fadhilah, Nurul (PT. Anagata Sembagi Education, 2024)
This research was carried out in Jaya Setia Village, Pasar Muara Bungo District. This research was carried out from February 20 2014 to May 20 2014. The aim of this research was to determine the effect of administering a dose of Azolla compost and to determine the correct dose of Azolla compost for the growth of oil palm seedlings. The design used in this research was a Completely Randomized Design (CRD) with 5 treatments and 4 replications, the treatments were as follows: A0 (No treatment), A1 (Azolla Compost 125 g/polybag), A2 (Azolla Compost 250 g/ polybag), A3 (Azolla Compost 375 g/polybag) and A4 (Azolla Compost 500 g/polybag). The variables observed were plant height (cm), total leaf area (cm2), stem diameter (cm), increase in the number of fronds (stem), and root volume (ml). The research results showed that administering a dose of Azolla compost of 3.75 g/polybag had a real effect on plant height, total leaf area, increase in the number of fronds and root volume but had no real effect on stem diameter. Providing a dose of Azolla compost at a dose of 375 g/polybag is the best dose for the growth of oil palm seedlings.